Embodied Learning and Teaching Using the 4E Cognition Approach: Exploring Perspectives in Teaching Practices (Routledge Research in Educational Psychology, 2024)
This book operationalises the new field—EmLearning—that integrates embodiment and grounded cognition perspectives with education using the 4E approach as a guiding principle, which suggests that cognition is embodied, embedded, enacted, or extended. Chapters highlight empirical data, providing readers with research-based insight into the theoretical foundations of embodied cognition in learning, illustrated by practical examples. Ultimately, the volume contributes a radical understanding of embodied cognition, demonstrating the importance of the field to the educational system more broadly and suggesting a fundamental change to the way learning, education, and curriculum design are viewed and considered. Based on contemporary scientific findings, the book addresses the educational area with a focus on opening the embodied approach to a wider audience that will circulate the new knowledge and support their educational practices. Written with the purpose of contributing to a broad spectrum of academic educational fields, this book will be of use to postgraduates, researchers, and academics in the fields of higher education, educational psychology, teacher education, and teaching methodology and practice. Teachers and school politicians should also benefit from this volume more broadly.